(untitled) (Bangladesh Journal of Infectious Diseases, 2025)
Background: The issue of antimicrobial resistance is one of the worldwide health concerns since more and more organisms are becoming resistant to common antibiotics. Objective: The objective of the study was to determine the pattern of common organisms isolated from pus and wound swabs in relation to their antibiogram. Methodology: This retrospective analysis was conducted in the Department of Microbiology at Green Life Medical College & Hospital Ltd., Dhaka, Bangladesh which was carried out between July 2023 and June 2024 for a period of one year. Pus samples and wound swabs were subjected to culture and sensitivity testing. Information about the patients, isolated organisms, culture reports, and sensitivity analyses was gathered from the record book of the Department of Microbiology. Results: Gram-positive bacteria comprised 13.7% and gram-negative bacteria accounted for 86.3% of the organisms that grew in 71.7% of the total 1245 samples. The most often isolated bacterium from wound swabs and pus samples was Pseudomonas species (34.9%). Staphylococcus aureus (14.3%), Klebsiella species (12.5%) and Escherichia coli (10.5%) were the next most frequently isolated organisms. Among gram-negative bacteria, 14.8% were ESBL-producing organisms, and Klebsiella species were the most commonly isolated ESBL producers. The majority of the microorganisms had significant antibiotic resistance. The majority of gram-negative bacteria were resistant to amoxicillin, fluoroquinolones, co-trimoxazole, and cephalosporins. The most effective antibiotics against gram-negative bacteria were colistin, tigecycline, carbapenems, and piperacillin/tazobactam. Most gram-positive bacteria were resistant to co-trimoxazole and fluoroquinolones, while 100.0% of Staphylococcus aureus was susceptible to linezolid and vancomycin, and 35.2% of it was methicillin-resistant (MRSA). Conclusion: The most common isolated bacteria are Pseudomonas species followed by Staphylococcus aureus, Klebsiella species and Escherichia coli, which are resistant to the majority of the commonly used antibiotics. Bangladesh Journal of Infectious Diseases, June 2025;12(1):34-41